Fallow Replacement Crop (Cover Crops, Annual Forages, and Short-Season Grain Crops) Effects on Wheat and Grain Sorghum Yields - J. D. Holman; T. Roberts; S. Maxwell (Kansas Agricultural Experiment Station Research Reports, 2016)
Producers are interested in growing cover crops and reducing fallow. Growing a crop during the fallow period would increase profitability if crop benefits exceeded expenses. Benefits of growing a cover crop were shown in high rainfall areas, but limited information is available on growing cover crops in place of fallow in the semiarid Great Plains. A study was done from 2007–2016 that evaluated cover crops, annual forages, and short season grain crops grown in place of fallow. In the first experiment (2007-2012) the rotation was no-till wheat-fallow, and in the second experiment (2012-2016) the rotation was no-till wheat-grain sorghum-fallow. This report presents results from the second experiment. The previous crop affected wheat yield; however, growing a previous crop as hay or cover did not affect wheat yield. Wheat yield following the previous crop was dependent on precipitation during fallow and the growing season. In dry years (2011-2014), growing a crop during the fallow period reduced wheat yields, while growing a crop during the fallow period had little impact on wheat yield in wet years (2008-2010). The length of the fallow period also affected yields of the following wheat crop. Growing a cover or hay crop until June 1 affected wheat less than if a winter or spring crop were grown for grain, which was approximately the first week of July. Cover crops did not improve wheat or grain sorghum yields compared to fallow. To be successful, the benefits of growing a cover crop during the fallow period must be greater than the expense of growing it; plus compensate for any negative yield impacts on the subsequent crop. Cover crops always resulted in less profit than fallow, while annual forages often increased profit compared to fallow. The negative effects on wheat yields might be minimized with flex-fallow, which is the concept of only growing a crop in place of fallow in years when soil moisture at planting and precipitation outlook are favorable at the time of making the decision to plant.
Keywords: cover crops; annual forages; short-season grain crops; wheat; grain sorghum; yields; fallow replacement crops; sweet clover; hairy vetch; lentil; Austrian winter forage pea; Austrian winter grain pea; triticale